EFFECT OF THE DIFFERENT FEED COMBINATIONS ON GROWTH AND SURVIVAL RATE OF GURAMI (Osphronemus gouramy Lac.) LARVAE By - Rusdianto, Rusdianto; Aryani, Netti; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACKThis research was conducted in April - May 2018 at Fish Breeding Laboratory of Fisheries and Marine Faculty, University of Riau. The aim was to see the effect of different feed combinations on the growth of gouramy (Osphronemus gouramy Lac.) larvae. The method used in this study is the experimental method using a completely factor randomized design (CRD) and six treatments with three replications. The treatments applied in this study are: P1 = Giving Tubifex sp on the 1st-10th day + Moina sp on 11st-20th day + boiled chicken egg yolk on 21st-30th day + shrimp pellets on 31st-40th day. P2 = Giving Tubifex sp on the 1st-10th day + boiled chicken egg yolk on 11st-20th day + Moina sp on 21st-30th day + shrimp pellets on 31st-40th day. P3 = Giving Tubifex sp on the 1st-10th day + shrimp pellets on 11st-20th day + Moina sp on 21st-30th day + boiled chicken egg yolk on 31st-40th day. P4 = Giving Tubifex sp on the 1st-10th day + Moina sp on 11st-20th day + shrimp pellets on 21st-30th day + boiled chicken egg yolk on 31st-40th day. P5 = Giving Tubifex sp on the 1st-10th day + boiled chicken egg yolk on 11st-20th day + shrimp pellets on 21st-30th day + Moina sp on 31st-40th day. P6 = Giving Tubifex sp on the 1st-10th day + shrimp pellets on 11st-20th day + boiled chicken egg yolk on 21st-30th day + Moina sp on 31st-40th day. The results showed that the best combination of feed for the growth of gouramy larvae are P4, with absolute weight growth 0,26 g, specific growth rates 5,67%, absolute length growth 3,23 cm, and survival rate 76,67%. Temperatures range from 26-29oC, pH 6.4-7.1 and Dissolved Oxygen 4.2-5.2 mg/L. Keywords: Feed combination, Larvae, Guramy (Osphronemus gouramy Lac)